PERAN TERAPIS GIGI DAN MULUT DALAM MENCEGAH STUNTING - I Gede Surya Kencana; Made Budi Artawa; nyoman gejir (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
Currently, Indonesia's priority health issue is being heated with the term stunting. Stunting is a health problem that stems from malnutrition which results in a child's height being lower than the height of other children of the same age. A person who is malnourished has a tendency to other health problems, one of which is dental problems. The factors that influence the growth and development of children are nutritional status, sleep patterns, dental health, motor development, and the role of the family in applying discipline to children. Children who get adequate food consumption, the value of their nutritional status will be good and balanced so that it can affect the growth and development of children. Assessment and evaluation of nutritional status is one of the important components in supporting the continuity of the process of growth and development of children. The role of the Dental and Oral Therapist consists of fostering/developing community participation capabilities in self-maintenance efforts in the UKGM program, care services for vulnerable groups, including: school children, groups of pregnant women, breastfeeding and pre-school children. Conclusion The role of dental and oral therapists is needed in supporting the reduction of stunting, namely in the care of dental and oral health services in collaboration with other health workers.